Retelling the computability - Cafezeiro, Isabel (2010)
This article retells the history of computabilty in the period from 1900 to 1936 under the light of the Science and Technology Studies. The narrative focuses on the contingencies at the time of the establishment of Hilbert’s Program, and follows the unfolding of the events until Gödel’s Theorem and the formulation of the Church Thesis. It takes an interdisciplinary approach, which applies, experiments and discusses different strategies to follow the construction of scientific knowledges having computability as its focus.